2008
DOI: 10.1111/j.1532-5415.2007.01601.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Vitamin D and Inflammation with the 6‐Minute Walk and Frailty in Patients with Heart Failure

Abstract: Twenty-five-hydroxyvitamin D and hsCRP levels may contribute to lower aerobic capacity and frailty in patients with heart failure. A longitudinal study will further define the role of 25OHD and hsCRP on muscle strength and functional decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
108
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 159 publications
(117 citation statements)
references
References 73 publications
6
108
1
2
Order By: Relevance
“…(10,(16)(17)(18)(19)(20)(21)(22) It has been shown that ambulation time over an 8-ft walkway correlated with higher serum 25(OH)D concentrations. (10,18) Gerdhem and colleagues (19) also have reported a positive significant linear correlation with usual walking speed in a cohort of 986 elderly women.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(10,(16)(17)(18)(19)(20)(21)(22) It has been shown that ambulation time over an 8-ft walkway correlated with higher serum 25(OH)D concentrations. (10,18) Gerdhem and colleagues (19) also have reported a positive significant linear correlation with usual walking speed in a cohort of 986 elderly women.…”
Section: Discussionmentioning
confidence: 99%
“…Second, previous studies used different cutoff values for abnormal serum 25(OH)D concentrations ranging from 10 to 30 ng/mL, (10,(16)(17)(18)(19)(20)(21)(22) which also may explain the divergences. From a historical point of view, normal vitamin D concentrations have been defined by the avoidance of adverse health consequences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations